Impact of Payload Hydrophobicity on the Stability of Antibody-Drug Conjugates - Bücheler, Jakob; Winzer, Matthias; Tonillo, Jason; Weber, Christian; Gieseler, Henning (Molecular Pharmaceutics, 2018)
In silico screening of toxin payloads typically employed in ADCs revealed a wide range of hydrophobicities and sizes as measured by logP and topological polar surface area (tPSA) values. These descriptors were used to identify three nontoxic surrogate payloads that encompass the range of hydrophobicity defined by the ADC toxin training set. The uniform drug to antibody ratio (DAR) ADCs were prepared for each surrogate payload by conjugation to the interchain cysteine residues of a model IgG1 subtype mAb. Linkage of these surrogate payloads to a common mAb with a matched DAR value allowed for preliminary analytical interrogation of the influence of payload hydrophobicity on global structure, self-association, and aggregation properties. The results of differential scanning fluorimetry and dynamic light scattering experiments clearly revealed a direct correlation between the destabilization of the native mAb structure and the increasing payload hydrophobicity. Also, self-association/aggregation propensity examined by self-interaction biolayer interferometry or size exclusion HPLC was consistent with increased conversion of the monomeric mAb to higher order aggregated species, with the degree of conversion directly proportional to the payload hydrophobicity. In summary, these findings prove that the payload-dependent structure destabilization and enhanced propensity to self-associate/aggregate driven by the increasing payload hydrophobicity contribute to reduced ADC stability and more complex behavior when assessing exposure and safety/efficacy relationships.
UnivIS-Import:2019-08-15:Pub.2018.nat.dchph.lphte.impact
Keywords: antibody-drug conjugates; protein aggregation; stability; conjugation; thermal analysis; physicochemical properties